Tingkat Partisipasi Masyarakat dalam Konservasi Penyu di Pantai Mampie Kecamatan Wonomulyo Kabupaten Polewali Mandar - Indhasari, Fitri; Abdullah, Muhammad Arafat; Najmiah (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2024)
Continuous maintenance, management and protection efforts are very important in turtle conservation to avoid extinction and damage. This research aims to calculate the level of community participation in turtle conservation activities using quantitative methods by distributing questionnaires. The population in this study was the entire Patoreang Mampie Hamlet community around the beach and the sample size was 40 respondents. The results of the research show that the level of community participation in the form of planning is included in the high category with a score of 2.71 because the community's environmental awareness is very high and the management of the turtle house has provided education related to maintaining and preserving the existence of turtles and the level of community participation in the form of management is included in the category high with a score of 2.75 as evidenced by community participation in turtle conservation activities, turtle festival activities, and the release of turtle hatchlings. Participation in the form of monitoring and evaluation is included in the high category with a score of 2.60, which means that the community often gives free time to monitor and oversee conservation activities around the turtle house area so that they run well and effectively. Keywords: Participation, community, conservation, turtle